Associations Between Psychopathy and the Trait Meta-Mood Scale in Incarcerated Males: A Combined Latent Variable- and Person-Centered Approach. (March 2020) - Garofalo, Carlo; Neumann, Craig S.; Mark, Daniel
The present study sought to replicate and extend current knowledge on the relevance of emotion regulation (ER) for psychopathy. In a large sample of incarcerated adult males ( N = 578), latent profile analysis (LPA) and structural equation modeling (SEM) were employed to examine person- and variable-centered associations between self-reported ER and both self-report and clinical ratings of psychopathy. With LPA, participants were classified into three profiles corresponding to low, medium, and high ER. The low-ER profile displayed higher affective traits across psychopathy assessments compared with the other profiles. The same pattern of findings was evident for overt behavioral features of psychopathy, but not for interpersonal traits. SEM results were consistent with LPA findings: interpersonal (positively), affective, and lifestyle (negatively) facets had unique associations with a superordinate ER latent variable. Findings replicate and extend prior associations between psychopathy and ER and suggest differential links between ER and affective and interpersonal traits of psychopathy.